ANALISIS PERBANDINGAN KINERJA PEGAWAI LAKI-LAKI DAN PEREMPUAN PADA BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN SUMBAWA - Suriyati, S; Kamaruddin, K (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to determine the differences in performance between male and female employees at the National Unity and Politics Agency of Sumbawa District. The type of this study was comparative study conducted to compare the performance of male employees (X1) with the performance of female employees (X2) at the National Unity and Politics Agency of Sumbawa District. The type of data used in this study was quantitative data obtained from official documents of the National Unity and Politics Agency of Sumbawa District, both published and unpublished. The data analysis technique used was comparative analysis using the average difference test, including the Shapiro-Wilk normality test and the average difference test using the paired samples statistics test, paired samples correlations test, and paired samples t-test. Based on the results of data analysis, the calculated t-value of 1.180 was smaller than the t-table value of 2.571 (1.180<2.571), while the significance value of the calculation results of 0.283 was greater than the real level value of 0.05 (0.283>0.05). Thus, it can be stated that there was not significant difference between the performance of male and female employees at the National Unity and Politics Agency of Sumbawa District. These results indicate that there is equality in terms of quantity and quality of performance produced by male and female employees in carrying out and completing work responsibilities. Male and female employees have the same contribution in achieving the goals and objectives set by the organization.